ANALYSIS EFFECT OF EXPORTS, IMPORTS, INFLATION AND FOREIGN DEBT ON FOREIGN EXCHANGE RESERVES IN INDONESIA - Sari, Impi Puspita; Ekaputri, Retno Agustina (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
The purpose of this study was to test and analyze how Indonesia's foreign exchange reserves were affected by imports, exports, inflation, and foreign debt. Regarding the relationship between Indonesia's foreign exchange reserves and imports, exports, inflation, and foreign debt for the 2019–2023 timeframe, there is a gap between theory and empirical data, which makes this study noteworthy. In order to regulate it and preserve economic stability, it is crucial to constantly track the movement of foreign exchange reserves. Data for the study were taken from official publications of Bank Indonesia (BI), the Central Statistics Agency (BPS), and the Indonesian Economic and Financial Statistics (SEKI). Monthly data was gathered for the study between 2019 and 2023. Using time series data for the 2019–2023 period, including monthly data and up to 60 series data, the sampling was carried out in Indonesia. using conventional hypothesis testing (t, f, and determination tests) and assumption checking (multicollinearity, normality, and heterokedasitas tests) to estimate multiple linear regression. While imports, exports, inflation, and foreign debt are independent factors, foreign exchange reserves are the dependent variable. The results of the study show that the dependent variable is influenced by two independent variables. Foreign exchange reserves are positively impacted by exports, but negatively by inflation. Furthermore, imports and foreign debt have no effect on foreign exchange reserves, making them independent variables that do not affect the dependent variable.